Factors That Influence Complience With Hypertension Patiens In The Kaliangkrik Puskesmas Working Area - Novela, Nona Ringgi; Supriyatno, Heru; Sarwono, Bambang; Widigdo, Dwi Ari Murti (Midwifery and Nursing Research, 2024)
Background: Hypertension is often referred to as the silent killer due to its potential to harm vital organs like the heart and kidneys without showing noticeable symptoms. Adherence to medication is crucial in preventing hypertension. Various factors, including medication-related issues, contribute to patient non-compliance. Many individuals fail to adhere to hypertension medication due to perceived side effects following consumption.Methods: This study uses a quantitative research method with a correlational research design. It employs a Cross-Sectional approach. The sampling technique used in this study is proportional simple random sampling. The sample consists of 88 respondents who suffer from hypertension. The research instrument used in this study is a questionnaire on factors influencing medication adherence among hypertension patients. To determine the relationships between these factors and medication adherence among hypertension patients, this study utilizes the Chi-Square test and Logistic Regression analysis.Conclusion: The most dominant factor influencing medication adherence in hypertension sufferers is the knowledge factor, followed by the second factor, namely the assumption of drug side effects. The most dominant factor influencing medication adherence in hypertensive patients is knowledge, followed by the second factor, which is assumptions about medication side effects.